Equations of optimal nonlinear filtration and interpolation for partially observed Markov processes - Voina, O. A.; Sidorov, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Recurrence relations are obtained for problems of optimal filtration and interpolation of partially observed discrete Markov chains. We present the system of differential equations for problems of optimal nonlinear filtration for Markov processes with continuous time and the system of inverse differential equations for problems of optimal nonlinear interpolation.